2016
DOI: 10.4067/s0716-10182016000100016
|View full text |Cite
|
Sign up to set email alerts
|

Panel Filmarray GI® en la detección de patógenos entéricos en deposiciones: experiencia preliminar

Abstract: Introduction: Gastrointestinal infections remain a major public health problem worldwide and its etiologic diagnosis is one of the main challenges. In molecular diagnostic techniques recently developed, the Filmarray GI ® panel allows detection of 23 pathogens (14 bacteria, virus 5 and 4 parasites) within an hour. Objective: To describe the experience of Filmarray GI ® panel in the Molecular Biology Laboratory of Clinica Las Condes. Method: A cross-sectional observational study that includes the results of 305… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
4
5
0
10
Order By: Relevance
“…The high frequency of co-detection in our study, particularly among the diarrheagenic E. coli pathotypes, is similar to prior studies using the FilmArray ® PCR in which co-detections were reported in 21–48% of positive samples 9,12,2123. Although co-detections in diarrheal diseases will likely be more commonly recognized with the increasing use of multiplexed molecular assays, whether such detections represent true coinfections of viable organisms or colonizers cannot be determined.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The high frequency of co-detection in our study, particularly among the diarrheagenic E. coli pathotypes, is similar to prior studies using the FilmArray ® PCR in which co-detections were reported in 21–48% of positive samples 9,12,2123. Although co-detections in diarrheal diseases will likely be more commonly recognized with the increasing use of multiplexed molecular assays, whether such detections represent true coinfections of viable organisms or colonizers cannot be determined.…”
Section: Discussionsupporting
confidence: 85%
“…In our study using multiplex PCR, 14 different pathogens were identified with an overall detection rate of 62.7%. This detection rate exceeds traditional laboratory detection methods2 and compares favorably to prior studies utilizing the FilmArray ® PCR in which detection rates ranged from 33% to 48% 9,12,2123. Thus, the breadth of pathogens surveyed and ease of use of this PCR platform make it well suited for epidemiologic studies, particularly in settings such as ours in which the traditional suite of culture media types, immunoassays, and uniplex PCR protocols used to survey a similarly broad range of pathogens would be difficult to implement due to limited human and laboratory resources.…”
Section: Discussionsupporting
confidence: 64%
“…Se realizó un estudio observacional, descriptivo de corte transverso, muestreo no probabilístico de casos consecutivos. (13,14) incluyendo algunos parásitos intestinales.…”
Section: Materiales Y Métodosunclassified
“…Un resultado interesante en este estudio fue la presencia de más de un patógeno en 7,8% de las muestras positivas que, si bien es similar a lo obtenido por otros estudios al utilizar metodologías convencionales, es mucho menor al compararlo con lo obtenido por Filmarray, con porcentajes que van del (14,15) 30,2% al 48,1%.…”
Section: Materiales Y Métodosunclassified
“…DEC infection prevalence has been underestimated, largely due to the lack of surveillance studies and the limited availability of molecular diagnostic techniques. Implementation of molecular techniques allowing simultaneous detection of multiple enteric pathogens, including DEC pathotypes, have shown that the prevalence of these pathotypes in diarrheal infections is higher than previously thought (Buss et al, 2015 ; Farfán et al, 2016 ).…”
Section: Introductionmentioning
confidence: 98%